Evolve of the chemical analysis of ignitable liquids for forensic purposes (2020)
Theme and scope: The objective of this review is to establish the evolve of the chemical analysis of ignitable liquids for forensic purposes, providing a current perspective of the methodologies and fundamental considerations for such analysis. Characteristics: The analysis of ignitable liquids has been characterized by evolve, as the analytical instrumentation has done; in this sense, the extraction process of ignitable liquids allows the recovery of a great variety of compounds, with significant sensitivity. On the other hand, gas chromatography has become the preferred technique for the analysis of fire accelerators, due to the volatility of the compounds present in such substances. Findings: The chemical investigations carried out have allowed the description of a series of factors that modify the composition of ignitable liquids residues after incineration and, therefore, the chromatographic profile obtained; These factors include the evaporation of the compounds, the matrix effect on incineration, pyrolysis, combustion processes, mixing with other substances for criminal purposes, the inherent variability of the ignitable liquids and the temperature reached in each incineration. Conclusions: The present review found that chemical research of ignitable liquids is focused on the sampling of the headspace to extract volatile compounds (using strips of activated carbon and solid phase microextraction SPME); Gas chromatography coupled to mass spectrometry (GC-MSD) is the most widely used analysis technique due to the volatility of the extract and the information obtained from mass spectra on the nature of the compounds. Finally, the different complications that arise in the analysis process are highlighted due to the variables degree of evaporation of the compounds, effect of the matrix on the incineration, pyrolysis, combustion processes, inherent variability of the accelerators and temperature reached in each incineration.